Letter : Help for the Workers of Spain Fund - Prestwich, J. W.
028-0201-001 TELEGRAPHIC ADDRESS: "WHOLESALE, MANCHESTER." TELEPHONE: BLACKFRIARS 1212. PLEASE ADDRESS YOUR REPLY: Co-operative Wholesale Society Limited. Secretary's Offices, 1, Balloon Street, MANCHESTER, 4. Our Reference: JWP/HB/MH. Your Reference: Personal 3rd September 1936. Dear Sir Walter, Help for the Workers of Spain Fund. On my return from London I have seen your letter of the 1st September, addressed to Mr. Lancaster, which as has been explained to you, was received here in his absence on vacation. The whole matter has been reviewed by my Directors in London this week and they have decided to make a grant of 200 guineas forthwith to your fund. We shall ask our Shareholders at the October, 1936, Quarterly Meeting to confirm this action. I am advising you immediately of this decision so that you can let me hear from you as to how you desire us to apply the grant. As a matter of information to you I would say that one of our constituent Societies has tabled a Notice of Motion for our October, 1936, Quarterly Meeting, as follows: "That we subscribe the sum of £500 to the International Co-operative Alliance for the Co-operators in Spain." Awaiting hearing from you further, I am, Yours sincerely, J. W. Prestwich. Assistant Secretary. Sir Walter Citrine, K.B.E. Trades Union Congress General Council. 292/946/28/201